SAT0391 The 8-Year Retention Rate of The First TNF-Inhibitor in The Treatment of Spondyloarthropathies: Real-Life Data from A Multicentric Local Registries. (15th July 2016) - Favalli, E.G.; Selmi, C.; Becciolini, A.; Biggioggero, M.; Ariani, A.; Santilli, D.; Fusaro, E.; Parisi, S.; Massarotti, M.; Marchesoni, A.; Meroni, P.L.
Abstract : Background: Long-term data on drug survival of TNF inhibitors (TNFi) in the treatment of spondyloarthropathies are still lacking. Objectives: The aim of the study is to analyze in a setting of real-life the 8-year retention rate of the first TNFi for the treatment of psoriatic arthritis (PsA) and axial spondyloarthritis (ax-SpA) and to compare the between-group discontinuation rates for each TNFi (infliximab [IFX], etanercept [ETN], and adalimumab [ADA]). Methods: Data were retrospectively extracted from four local registries including all patients affected by PsA and ax-SpA treated with a biologic drug between January 2005 and May 2015. The analysis was limited to patients treated with IFX, ETN, or ADA as first-line biologic agent, with at least 1-year follow-up period. The 8-year drug survival was evaluated by Kaplan-Meier method and the risk for discontinuation among the 3 treatment groups was compared by a stratified log-rank test. Results: The study population (614 patients) included 316 ax-SpA (69.9% male, mean age [±SD] 42.8 [±12.1] years, mean disease duration 7.2 [±7.9] years), treated with ADA (n=95), ETN (n=42), or IFX (n=179); and 298 PsA (51.7% male, mean age 47.8 [±12.1] years, mean disease duration 8.8 [±7.7] years), treated with ADA (n=108), ETN (n=89), or IFX (n=101). The overall median survival on treatment of the whole study population was 117.17 months (102.84 and >117.17 months for axSpA and PsA, respectively; p=NS). The overall retention rate was 66.2% (69.5% versus 62.8% in axSpA and PsA, respectively) at 5 years and 55.5% (57.2% versus 53.4% in axSpA and PsA, respectively) at 8 years. No significant differences emerged in the comparison among ADA, ETN, and IFX in both ax-SpA group (p=0.1065) and PsA group (p=0.06). IFX and ETN showed similar survival rates in PsA and axSpA (HR 1.252, 95% CI 0.600–2.608, and HR 1.224, 95% CI 0.8441–1.774, respectively), whereas ADA showed a significantly higher survival in axSpA compared to PsA (HR 1.775, 95% CI 1.045–3.013). Overall, 265 (43.1%) patients (129 [43.2%] PsA and 133 [42.1%] axSpA), stopped the first course TNFi. Inefficacy led to discontinuation in 115 (18.7%) patients (65 [21.8%] PsA and 50 [15.8%] axSpA), without significant differences between the two disease groups (p=0.1076). Adverse events led to discontinuation in 88 (14.3%) patients, (43 [14.4%] PsA and 45 [14.2%] axSpA), without significant differences between PsA and axSpA (p=0.9049). Conclusions: In a real-life setting, the 8-year retention rate of the first TNFi in the treatment of spondyloarthropathies was about 50%, with no significant difference between ax-SpA and PsA. The risk of stopping IFX and ETN treatment was similar in both ax-SpA and PsA group, whereas ADA showed a higher survival in axSpA group. Disclosure of Interest: None declared